Periodic Components of the Fatou Set of Three Transcendental Entire Functions and Their Compositions - Subedi, Bishnu Hari; Singh, Ajaya (Journal of Nepal Mathematical Society, 2020)
We prove that there exist three different transcendental entire functions that can have infinite number of domains which lie in the different periodic component of each of these functions and their compositions.